CHARACTERISTICS OF WOMEN WHO EXPERIENCE ANTEPARTUM HAEMORRHAGE AND POSPARTUM HAEMORRHAGE AT EFARINA ETAHAM HOSPITAL BERASTAGI KARO - Doortua; Sri Wahyuni; Maswan; Renta Manurung; Putri; Afni Fazira (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
Antepartum bleeding is vaginal bleeding in pregnancy over 28 weeks or more. Because antepartum bleeding occurs at gestational age above 28 weeks, it is often called or classified as bleeding in the third trimester (Manuaba, 2007) while postpartum hemorrhage according to the World Health Organization (WHO) in 2006, namely partly puerperal blood loss of 500 ml or more that occurs after the child is born. The purpose of this study was to find out the characteristics of mothers who experienced antepartum bleeding and postpartum hemorrhage at Efarina Etaham Berastagi Hospital in the 2013-2016 period. The type of research used in this study is a retrospective descriptive study. The population in this study were medical records of mothers who experienced antepartum and postpartum hemorrhage at Efarina Etaham Berastagi Hospital, Karo District in 2013 - 2016. The number of medical records of mothers who experienced antepartum hemorrhage was 17 cases of antepartum and 25 cases of postpartum hemorrhage. From the results of a study on the characteristics of mothers who experienced antepartum and postpartum hemorrhage which was conducted at Efarina Etaham Berastagi Hospital, bleeding data was obtained based on antepartum age 5 35 years 8 people (47.1%), postpartum age 20 years 17 people (68.0%) , 8 people (47.1%) high school antepartum education, 13 high school postpartum education people (52.0), and antepartum family income « ​​Rp. 1200,000 9 people (52.9%), postpartum family income « ​​Rp. 1200,000 13 people (52.0%), Based on the results of the study, 10 people (58.6%) had multiparous antepartum bleeding, 9 people (52.9%) -28 weeks of gestation, 11 people (64.7%) had a history of prenatal bleeding, 15 people had a history of prenatal bleeding. (88.2%), type of history of pregnancy Sectio (SC) 14 people (82.4%). The results of the research data were 11 people (44%) with multiparous Postpartum Hemorrhage, 9 people (36%) had intervals of delivery »3 years and 2-3 years, 17 people (68%) had retained placenta due to bleeding, 20 people had a history of pre-delivery disease (80 %), type of history of normal pregnancy 22 people (88%). As input material and information in an effort to reduce the morbidity of antepartum bleeding and postpartum bleeding, especially at Efarina Etaham Berastagi Hospital. the cause of placenta previa bleeding was 11 people (64.7%), history of prenatal illness in 15 people (88.2%), type of history of pregnancy Sectio (SC) 14 people (82.4%). The results of the research data were 11 people (44%) with multiparous Postpartum Hemorrhage, 9 people (36%) had intervals of delivery »3 years and 2-3 years, 17 people (68%) had retained placenta due to bleeding, 20 people had a history of pre-delivery disease (80 %), type of history of normal pregnancy 22 people (88%). As input material and information in an effort to reduce the morbidity of antepartum bleeding and postpartum bleeding, especially at Efarina Etaham Berastagi Hospital. the cause of placenta previa bleeding was 11 people (64.7%), history of prenatal illness in 15 people (88.2%), type of history of pregnancy Sectio (SC) 14 people (82.4%). The results of the research data were 11 people (44%) with multiparous Postpartum Hemorrhage, 9 people (36%) had intervals of delivery »3 years and 2-3 years, 17 people (68%) had retained placenta due to bleeding, 20 people had a history of pre-delivery disease (80 %), type of history of normal pregnancy 22 people (88%). As input material and information in an effort to reduce the morbidity of antepartum bleeding and postpartum bleeding, especially at Efarina Etaham Berastagi Hospital.